PENINGKATAN MINAT BERWIRAUSAHA MAHASISWA MELALUI MEDIA SOSIAL DAN LINGKUNGAN KELUARGA - Sri Lestari Prasilowati; Nanda Hidayati (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
This study seeks to develop research on the concept of increasing student interest in entrepreneurship through social media and the family environment which are expected to become young entrepreneurs to support reducing unemployment and increasing the country's economy. This study aims to analyze the relationship between social media variables on student entrepreneurship interest, the family environment relationship with student entrepreneurship interest. This research method uses a quantitative survey. Data collection was carried out using a questionnaire (Likert scale) via Google form and distributed via the WhatsApp group. The research was conducted in August - December 2022 with 100 research respondents at IPWIJA University, using a proportional random sampling technique and using the Solvin formula. Data analysis techniques in quantitative research use structural equation models (SEM) and statistical software SmartPLS 3.2.9. The restudy’s results showed positive and significant influence between family environment and social media variables on student interest in entrepreneurship. The practical implication of this research is that to increase students' interest in entrepreneurship, they must increase the variables of the family environment and social media